Penggunaan Teori Perturbasi untuk Menentukan Tingkat Energi Partikel pada Kotak Potensial Tiga Dimensi - Kharismawati, Indah (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2020)
Hamiltonian a known system in many matters does not guarantee that the equation can be resolved, e.g. due to minor disturbances such as electric fields or magnetic fields that can lead to slight changes in energy and its particle functions, for such issues it should be used disorder theory (perturbation theory). The perturbation theory can determine how much the result of the presence of disruption to energy levels and Eigen's functions. The energy possessed by particles in addition to being influenced by quantum numbers (nx, ny and nz) and the size of the potential box are also influenced by interference in the form of magnetic energy produced due to the motion of particles (electrons) in the core intrinsic magnetic field (proton) which affects the energy value does not appear due to the value of this magnetic energy disorder is very small, while for interference that is an extrinsic magnetic energy has shown a 10 (Tesla). The wider the size of the box then the energy that the particles have is smaller so that the energy level and the particle energy spectrum in the potential box will appear continuous. It can be concluded that the particle energy level relies on the length of the potential box, the quantum number of particles, and also the interference that particles have. Â Â